The management of Otitis Media with Effusion in children with cleft palate (mOMEnt): a feasibility study and economic evaluation - Iain Bruce; Nicola Harman; Paula Williamson; Stephanie Tierney; Peter Callery; Syed Mohiuddin; Katherine Payne; Elisabeth Fenwick; Jamie Kirkham; Kevin O’Brien (Health Technology Assessment, 2015)
Background: Cleft lip and palate are among the most common congenital malformations, with an incidence of around 1 in 700. Cleft palate (CP) results in impaired Eustachian tube function, and 90% of children with CP have otitis media with effusion (OME) histories. There are several approaches to management, including watchful waiting, the provision of hearing aids (HAs) and the insertion of ventilation tubes (VTs). However, the evidence underpinning these strategies is unclear and there is a need to determine which treatment is the most appropriate. Objectives: To identify the optimum study design, increase understanding of the impact of OME, determine the value of future research and develop a core outcome set (COS) for use in future studies. Design: The management of Otitis Media with Effusion in children with cleft palate (mOMEnt) study had four key components: (i) a survey evaluation of current clinical practice in each cleft centre; (ii) economic modelling and value of information (VOI) analysis to determine if the extent of existing decision uncertainty justifies the cost of further research; (iii) qualitative research to capture patient and parent opinion regarding willingness to participate in a trial and important outcomes; and (iv) the development of a COS for use in future effectiveness trials of OME in children with CP. Setting: The survey was carried out by e-mail with cleft centres. The qualitative research interviews took place in patients’ homes. The COS was developed with health professionals and parents using a web-based Delphi exercise and a consensus meeting. Participants: Clinicians working in the UK cleft centres, and parents and patients affected by CP and identified through two cleft clinics in the UK, or through the Cleft Lip and Palate Association. Results: The clinician survey revealed that care was predominantly delivered via a ‘hub-and-spoke’ model; there was some uncertainty about treatment strategies; it is not current practice to insert VTs at the time of palate repair; centres were in a position to take part in a future study; and the response rate to the survey was not good, representing a potential concern about future co-operation. A COS reflecting the opinions of clinicians and parents was developed, which included nine core outcomes important to both health-care professionals and parents. The qualitative research suggested that a trial would have a 25% recruitment rate, and although hearing was a key outcome, this was likely to be due to its psychosocial consequences. The VOI analysis suggested that the current uncertainty justified the costs of future research. Conclusions: There exists significant uncertainty regarding the best management strategy for persistent OME in children with clefts, reflecting a lack of high-quality evidence regarding the effectiveness of individual treatments. It is feasible, cost-effective and of significance to clinicians and parents to undertake a trial examining the effectiveness of VTs and HAs for children with CP. However, in view of concerns about recruitment rate and engagement with the clinicians, we recommend that a trial with an internal pilot is considered. Funding: The National Institute for Health Research Health Technology Assessment programme. This study was part-funded by the Healing Foundation supported by the Vocational Training Charitable Trust who funded trial staff including the study co-ordinator, information systems developer, study statistician, administrator and supervisory staff.